Padre Miguelinho :o intelectual, o professor, o revolucionário - vozes que se fazem ouvir - Moreira, Keila Cruz (2005)
This research work worries in building the history of the natalense priest Miguel Joaquim of Almeida Castro, Miguelinho, I don't just eat one of the heroes and martyrs of the Revolution From Pernambuco of 1817, as bill the traditional history, but also the educated man, the intellectual and the admired teacher. The studied period understands the beginning of the century XIX, when priest Miguelinho comes back to Brazil, coming of Portugal, to assume teacher's occupation in the Seminar of Olinda, and it ends in the year of 1817, marked by the Revolution From Pernambuco, one of the most important movements in the fight for the liberation of Brazil of the Portuguese domain. Miguelinho, one of the leaders of the Revolution, that also reached the provinces of Paraíba and of Rio Grande do Norte, it was executed by the real troops. Like this, he tries to understand the Priest's conflicting relationship, while representative clergyman, of a Church that almost obtained a religious monopoly, and your ideals per centuries more gone back to a social and economical order of Illumines, that even certain point condemned the attitude of the own Church. The objective, then, is to understand through the path of priest's Miguelinho life, not only the intellectual, the teacher and the revolutionary, but the representation of your political and pedagogic-educational ideas in a die historical moment and the creation of the republican myth, looking for the plurality of an universe that seeks, per times, to flee of our theoretical context